Graphite crucible repair material and graphite crucible repair method

By using graphite crucible repair materials containing coke raw materials, aluminum silicate and acrylic emulsion, combined with heating and pressing, vacuum environment and graphitization treatment, the problem of graphite crucibles prone to cracks and damage in high temperature environments in the prior art is solved, and the problem of graphite crucibles being easily cracked and damaged in high temperature environments is realized. Increases service life and safety, and reduces resource waste.

CN119080495BActive Publication Date: 2025-02-11BTR NEW MATERIAL GRP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411381902.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-11
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Existing graphite crucible repair technology is prone to cracks and damage in high temperature environments, and the repair agent used may introduce metal foreign matters, resulting in poor product quality.

Method used

A graphite crucible repair material, including coke raw material or graphite tail material, aluminum silicate salt and acrylic emulsion, is used to prepare a block repair material by heating and pressing, and combine it with the crucible with graphite bolts, combined with vacuum environment and graphitization treatment. , improve the adhesion and strength of repair materials.

Benefits of technology

Effectively improve the service life and safety of graphite crucibles, reduce the risk of cracks or damage again in high temperature environments, and realize the reuse of coke raw materials and graphite tail materials with smaller particle sizes, reducing the Waste of resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119080495B_ABST
    Figure CN119080495B_ABST
Patent Text Reader

Abstract

The present application relates to a graphite crucible repair material and a graphite crucible repair method. The graphite crucible repair material comprises: 10 to 35 parts by weight of coke raw material and / or graphite tailings; 5 to 15 parts by weight of aluminum silicate; and 10 to 20 parts by weight of acrylic emulsion; wherein the median particle size of the coke raw material and / or graphite tailings is ≤ 5 μm. The graphite crucible repair material and the graphite crucible repair method of the present application can achieve comprehensive repair and reinforcement of the cracks in the graphite crucible and the entire graphite crucible, effectively solving the problem that the repaired graphite crucible is prone to cracks and breakage in a high temperature environment, thereby improving the service life and safety of the graphite crucible.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of crucible processing, in particular to a graphite crucible repairing material and a graphite crucible repairing method. Background Art

[0002] With the rapid development of the global new energy market, especially the rapid rise of the lithium battery industry, the negative electrode graphite purification and coating industry has been greatly promoted. In the production process of negative electrode materials, the roller kiln is the main carbonization equipment, and the graphite sagger (crucible) inside it is an indispensable consumable. These crucibles are repeatedly used in high temperature environments for a long time, not only the strength gradually decreases, but also it is easy to crack or break due to the characteristics of the material itself. Due to the long crucible preparation cycle, high cost and complex process, it is very necessary to repair and reuse the damaged or expired crucibles.

[0003] The crucible repair technology currently on the market mainly relies on various repair agents, such as the crucible repair agent and repair method disclosed in CN117327470A. This method uses a specific repair agent to repair the crucible at high temperature. Although it can improve the strength of the crucible to a certain extent and reduce the occurrence of cracks and breakage, the repair agent used will introduce metal foreign matter, such as titanium powder, copper powder, etc. during carbonization. These metal foreign matter may cause the metal content in the product to exceed the standard in the subsequent production process, and then cause internal short circuits after the battery is prepared, and even cause battery explosions. In addition, most existing repair agents are single-phase structures, and the repaired crucible is still prone to cracks and breakage in a high temperature environment.

[0004] In addition, in the production process of negative electrode materials, coke raw materials or graphite are mostly needed, but coke raw materials and graphite need to go through the crushing process in the production process of negative electrode materials, which inevitably produces a large amount of tailings (micro powder). These "tailings" are too small to be directly used in production, and most of them can only be calcined as a carburizer. However, this method makes the utilization rate of tailings low. At the same time, the accumulation of a large amount of tailings also occupies a lot of storage space, increasing the difficulty of management. Summary of the invention

[0005] The present application provides a graphite crucible repair material and a graphite crucible repair method, which can achieve comprehensive repair and reinforcement of graphite crucible cracks and the entire graphite crucible, effectively solving the problem that the repaired graphite crucible is prone to cracks and breakage in a high temperature environment, thereby improving the service life and safety of the graphite crucible.

[0006] In a first aspect, the present application provides a graphite crucible repair material, the repair material comprising:

[0007] 10-35 parts by weight of coke raw material and / or graphite tailings;

[0008] 5-15 parts by weight of aluminum silicate;

[0009] 10-20 parts by weight of acrylic emulsion;

[0010] Wherein, the median particle size of the coke raw material and / or the graphite tailing is ≤5 μm.

[0011] In some embodiments, the graphite crucible repair material further includes 5 to 10 parts by weight of polyethylene glycol.

[0012] In some embodiments, the graphite crucible repair material further includes 5 to 10 parts by weight of dioctyl phthalate.

[0013] In some embodiments, the graphite crucible repair material further includes 1 to 5 parts by weight of a polysaccharide compound, and the polysaccharide compound includes yellow dextrin.

[0014] In some embodiments, the graphite crucible repair material further includes 1 to 5 parts by weight of isocyanate.

[0015] In some embodiments, the repair material is subjected to a heating and pressing process to obtain a block-shaped repair material; wherein the thickness of the block-shaped repair material is 2 mm to 10 mm, and a plurality of bolt through holes are provided on the surface of the block-shaped repair material.

[0016] In some embodiments, the pressure of the heating and pressing treatment is 800T~1200T.

[0017] In some embodiments, the temperature of the heating and pressing treatment is 2000°C to 2400°C.

[0018] In some embodiments, the heating and pressing treatment is performed for 60 min to 90 min.

[0019] In some embodiments, the pressure increase rate and pressure release rate of the heating and pressing process are independently less than 10 T / min.

[0020] In a second aspect, the present application provides a method for repairing a graphite crucible, wherein the graphite crucible repair material according to the first aspect is used to repair the crucible, and the repair method comprises the following steps:

[0021] Processing the crack of the graphite crucible and opening a plurality of threaded holes on the surface of the graphite crucible;

[0022] Applying a graphite crucible repair material to the crack of the graphite crucible, and combining the block-shaped repair material with the graphite crucible using a graphite bolt;

[0023] Placing the graphite crucible in an inert atmosphere environment at 1000° C. to 1150° C. for coke removal treatment;

[0024] In a vacuum environment, the graphite crucible is impregnated with a binder at 200°C-700°C, and then heated to 2400°C-2800°C for graphitization.

[0025] In some embodiments, the inert ambient atmosphere includes at least one of nitrogen, argon, helium, and neon.

[0026] In some embodiments, the heating rate of the decoking process is 0.2°C / min to 1°C / min.

[0027] In some embodiments, the decoking process lasts for 1 hour to 4 hours.

[0028] In some embodiments, the vacuum degree in the vacuum environment is less than 500 Pa.

[0029] In some embodiments, the cooling rate from the decoking treatment to the immersion treatment is 0.2° C. / min to 1° C. / min.

[0030] In some embodiments, the immersion treatment time is 1 h to 4 h.

[0031] In some embodiments, the graphitization treatment time is 2h~4h.

[0032] In some embodiments, the heating rate of the graphitization treatment is 0.2°C / min to 1°C / min.

[0033] In some embodiments, after the graphitization treatment, the repair method further comprises: cooling the graphite crucible to room temperature and then taking it out for surface polishing until the surface of the graphite crucible is smooth.

[0034] In some embodiments, the binder includes at least one of an asphalt solution, an acrylic emulsion, an aqueous polyurethane, an emulsion, and a polyvinyl alcohol emulsion.

[0035] In some embodiments, the binder includes 8 to 15 parts by weight of aluminum silicate, 10 to 20 parts by weight of acrylic emulsion, and 1 to 10 parts by weight of dioctyl phthalate.

[0036] Compared with the prior art, the technical solution of the present application has at least the following beneficial effects:

[0037] The graphite crucible repair material provided by the present application can make the repair material and the material of the graphite crucible have good compatibility and adhesion by reasonably adjusting the raw material ratio of each component in the repair material, so that the cracks in the graphite crucible can be tightly filled, and the repaired graphite crucible can be reduced to reduce the recurrence of cracks or damage during use. At the same time, through the synergistic effect of aluminum silicate and acrylic emulsion, the strength and wear resistance of the graphite crucible material can be enhanced, and the service life and safety of the graphite crucible can be improved. In addition, the present application uses coke raw materials and graphite tailings with smaller particle sizes as components of the repair material, thereby achieving the reuse of coke raw materials and graphite tailings with smaller particle sizes, thereby effectively reducing resource waste and improving resource utilization.

[0038] The repair method of the graphite crucible provided in the present application processes the crack of the graphite crucible, and uses graphite bolts to tightly connect the block repair material and the graphite crucible under the action of the graphite crucible repair material, thereby ensuring the firmness of the repair, simplifying the repair process, and improving the repair efficiency; then the graphite crucible is placed in a protective atmosphere for coke removal treatment, and the impurities introduced during the graphite crucible repair process can be removed by the coke removal treatment, thereby ensuring the quality and safety of the negative electrode product, and at the same time, the repair gap can be effectively filled to improve the mechanical strength of the graphite crucible; then the graphite crucible is impregnated with a binder in a vacuum environment, and the binder can be filled into the pores of the graphite crucible by the impregnation treatment under a vacuum environment, thereby improving the volume density and strength of the graphite crucible; finally, the carbon-containing raw material components in the repair material, the block repair material and the binder can be converted into a graphite material with higher strength by graphitization treatment, thereby improving the compatibility of the block repair material and the graphite crucible, thereby improving the high temperature resistance and mechanical strength of the graphite crucible and extending the service life of the graphite crucible. The above-mentioned graphite crucible repair method is simple and efficient. The repaired graphite crucible has excellent high temperature resistance, volume density and mechanical strength, and can reduce the damage and cracking of the graphite crucible during use, thereby reducing the risk of kiln blockage and ensuring the smooth operation of the production line and the stability of production capacity. In addition, no harmful substances need to be added during the entire repair process, which is environmentally friendly and meets the requirements of sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0040] Figure 1 This is a schematic diagram of the structure of the block repair material prepared in Example 1 of the present application;

[0041] Figure 2 A schematic diagram of the structure of a graphite bolt provided in Example 1 of the present application;

[0042] Figure 3A schematic diagram of the structure of the graphite crucible after processing provided in Example 1 of the present application;

[0043] Figure 4 A schematic diagram of the combination of the block repair material and the graphite crucible provided in Example 1 of the present application;

[0044] Figure 5 A schematic diagram of the structure of a block repair material provided in Example 4 of the present application;

[0045] Figure 6 A schematic diagram of the structure of a graphite bolt provided in Example 4 of the present application;

[0046] Figure 7 A schematic diagram of the structure of the graphite crucible after processing provided in Example 4 of the present application;

[0047] Figure 8 A schematic diagram of the combination of a block repair material and a graphite crucible provided in Example 4 of the present application;

[0048] Fig. 9 A schematic diagram of testing the flexural strength of a graphite crucible provided in an embodiment of the present application;

[0049] Fig.10 A schematic diagram of a test of the compressive strength of a graphite crucible provided in an embodiment of the present application. DETAILED DESCRIPTION

[0050] In order to better understand the technical solution of the present invention, the embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0051] It should be clear that the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0052] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0053] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0054] In a first aspect, the present application provides a graphite crucible repair material, the graphite crucible repair material comprising:

[0055] 10-35 parts by weight of coke raw material and / or graphite tailings;

[0056] 5-15 parts by weight of aluminum silicate;

[0057] 10-20 parts by weight of acrylic emulsion;

[0058] Wherein, the median particle size of the coke raw material and / or graphite tailing is ≤5 μm.

[0059] The graphite crucible repair material provided by the present application can make the repair material and the material of the graphite crucible have good compatibility and adhesion by reasonably adjusting the raw material ratio of each component in the repair material, so that the cracks in the graphite crucible can be tightly filled, and the repaired graphite crucible can be reduced to reduce the recurrence of cracks or damage during use. At the same time, through the synergistic effect of aluminum silicate and acrylic emulsion, the strength and wear resistance of the graphite crucible material can be enhanced, and the service life and safety of the graphite crucible can be improved. In addition, the present application uses coke raw materials and graphite tailings with smaller particle sizes as components of the repair material, thereby achieving the reuse of coke raw materials and graphite tailings with smaller particle sizes, thereby effectively reducing resource waste and improving resource utilization.

[0060] In some embodiments, the repair material is subjected to a heating and pressing process to obtain a block-shaped repair material.

[0061] Optionally, the coke raw material in the graphite crucible repair material can specifically be 10 parts by weight, 12 parts by weight, 15 parts by weight, 16 parts by weight, 18 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 32 parts by weight or 35 parts by weight, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0062] Optionally, the graphite tailings in the graphite crucible repair material can specifically be 10 parts by weight, 12 parts by weight, 15 parts by weight, 16 parts by weight, 18 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 32 parts by weight or 35 parts by weight, but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0063] Optionally, the aluminum silicate in the graphite crucible repair material can be 5 parts by weight, 6 parts by weight, 8 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight or 15 parts by weight, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0064] Optionally, the acrylic emulsion in the graphite crucible repair material can be 10 parts by weight, 11 parts by weight, 12 parts by weight, 14 parts by weight, 16 parts by weight, 18 parts by weight or 20 parts by weight, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0065] In some embodiments, the graphite crucible repair material also includes 5 to 10 parts by weight of polyethylene glycol, specifically 5 parts by weight, 5.5 parts by weight, 6 parts by weight, 6.5 parts by weight, 7 parts by weight, 7.5 parts by weight, 8.4 parts by weight, 9.2 parts by weight or 10 parts by weight, etc., and of course other values ​​within the above range are also possible, which are not limited here.

[0066] In some embodiments, the ink crucible repair material also includes 5 to 10 parts by weight of dioctyl phthalate (DOP), specifically 5 parts by weight, 5.5 parts by weight, 6 parts by weight, 6.3 parts by weight, 7 parts by weight, 7.5 parts by weight, 8 parts by weight, 8.5 parts by weight, 9.2 parts by weight, 9.6 parts by weight or 10 parts by weight, etc., and of course other values ​​within the above range are also possible, which are not limited here.

[0067] In some embodiments, the graphite crucible repair material further includes 1 to 5 parts by weight of a polysaccharide compound, specifically 1 part by weight, 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight, 3 parts by weight, 3.3 parts by weight, 4 parts by weight, 4.5 parts by weight or 5 parts by weight, etc., and of course other values ​​within the above range are also possible, which are not limited here. The polysaccharide compound can specifically be yellow dextrin.

[0068] In some embodiments, the graphite crucible repair material also includes 1 to 5 parts by weight of isocyanate, specifically 1 part by weight, 1.2 parts by weight, 1.5 parts by weight, 2 parts by weight, 3 parts by weight, 3.3 parts by weight, 4 parts by weight, 4.8 parts by weight, 5 parts by weight, etc., and of course other values ​​within the above range are also possible, which are not limited here.

[0069] The present application controls the weight ratio of each component in the repair material within the above range, so that the repair material and the block repair material have good compatibility and adhesion with the graphite crucible material, can tightly fill the cracks in the graphite crucible, and reduce the recurrence of cracks or breakage in the repaired graphite crucible during high-temperature use.

[0070] In some embodiments, the median particle size of the coke raw material and the graphite tailings is ≤5μm, and can be 5μm, 4.8μm, 4.5μm, 4μm, 3.5μm, 3μm, 2.5μm, 2.3μm, 2.0μm, 1.8μm, 1.5μm, 1.1μm, 0.9μm, 0.5μm or 0.3μm, etc., and of course, it can also be other values ​​within the above range, which are not limited here. The repair material of the present application uses coke raw materials and graphite tailings with smaller particle sizes as components of the repair material, thereby realizing the reuse of coke raw materials and graphite tailings with smaller particle sizes, thereby effectively reducing resource waste and improving resource utilization. At the same time, the coke raw materials and graphite tailings can be converted into graphite materials with higher strength after high-temperature treatment. These graphite materials have the same composition as the graphite crucible, which can effectively improve the compatibility and adhesion between the repair material and the block repair material and the graphite crucible, and reduce the repaired graphite crucible from cracking or damage again during use.

[0071] In some embodiments, the coke feedstock includes one of pitch coke, needle coke, petroleum coke, and wrought coke.

[0072] In some embodiments, the graphite tailings include at least one of natural graphite tailings and artificial graphite tailings. Specifically, the graphite tailings can be flaky, such as natural flake graphite tailings, or spherical graphite tailings, which can be selected according to actual needs and are not limited here.

[0073] In some embodiments, the repair material is subjected to a heating and pressing process to obtain a block-shaped repair material.

[0074] In some embodiments, the thickness of the block repair material is 2 mm to 10 mm, specifically 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, or 10 mm, etc. Of course, it can also be other values ​​within the above range, which is not limited here. It can be understood that the thickness of the block repair material within the above range can enhance the repair strength and improve the repair effect, which is conducive to extending the service life of the graphite crucible and ensuring the long-term use safety of the graphite crucible.

[0075] In some embodiments, a plurality of bolt through holes are provided on the surface of the block repair material, and graphite bolts can tightly connect the block repair material and the graphite crucible through these bolt through holes, thereby effectively reducing the recurrence of cracks or breakage of the repaired graphite crucible during use, which is beneficial to extending the service life of the graphite crucible.

[0076] In some embodiments, the pressure of the heating and pressing treatment is 800T to 1200T, specifically 800T, 850T, 900T, 950T, 1000T, 1050T, 1100T, 1150T or 1200T, etc., and of course, other values ​​within the above range are also possible, which are not limited here. Controlling the pressure of the heating and pressing treatment within the above range can promote the uniform distribution of components in the block repair material, improve the density of the block repair material, reduce cracks and defects in the block repair material, and improve the compressive strength and flexural strength of the block repair material.

[0077] In some embodiments, the temperature of the heating and pressing treatment is 2000°C~2400°C, specifically 2000°C, 2100°C, 2200°C, 2300°C or 2400°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0078] In some embodiments, the time for heating and pressing treatment is 60 min to 90 min, specifically 60 min, 65 min, 68 min, 70 min, 75 min, 80 min, 85 min, 86 min, 88 min or 90 min, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0079] In the present application, the temperature and time of the heating and pressing treatment are controlled within the above-mentioned range, which is beneficial to promote the bonding between the component particles in the block repair material, reduce the porosity of the block repair material, and increase the density of the block repair material, which is beneficial to improve the uniformity and consistency of the block repair material, and reduce the occurrence of cracks and breakage of the block repair material during use, thereby improving the compressive strength and flexural strength of the repaired graphite crucible.

[0080] In some embodiments, the pressure increase rate and pressure release rate of the heating and pressing treatment are each independently less than 10 T / min, and can be specifically 9.8 T / min, 9.5 T / min, 8.9 T / min, 8.5 T / min, 7 T / min, 6.4 T / min, 5 T / min, 4 T / min, 3 T / min, 2 T / min or 1 T / min, etc., and of course, it can also be other values ​​within the above range, which are not limited here.

[0081] In a second aspect, the present application provides a method for repairing a graphite crucible, wherein the graphite crucible repair material described in the first aspect is used to repair the crucible, and the repair method comprises the following steps:

[0082] Step S100, processing the crack of the graphite crucible and opening a plurality of threaded holes on the surface of the graphite crucible;

[0083] Step S200, applying a graphite crucible repair material to the crack of the graphite crucible, and combining the block-shaped repair material and the graphite crucible with a graphite bolt;

[0084] Step S300, placing the graphite crucible in an inert atmosphere environment at 1000° C. to 1150° C. for coke removal;

[0085] Step S400, in a vacuum environment, the graphite crucible is impregnated with a binder at 200°C-700°C, and then the temperature is raised to 2400°C-2800°C for graphitization.

[0086] The repair method of the graphite crucible provided in the present application processes the crack of the graphite crucible, and uses graphite bolts to tightly connect the block repair material and the graphite crucible under the action of the graphite crucible repair material, thereby ensuring the firmness of the repair, simplifying the repair process, and improving the repair efficiency; then the graphite crucible is placed in a protective atmosphere for coke removal treatment, and the impurities introduced during the graphite crucible repair process can be removed by the coke removal treatment, thereby ensuring the quality and safety of the negative electrode product, and at the same time, the repair gap can be effectively filled to improve the mechanical strength of the graphite crucible; then the graphite crucible is impregnated with a binder in a vacuum environment, and the binder can be filled into the pores of the graphite crucible by the impregnation treatment under a vacuum environment, thereby improving the volume density and strength of the graphite crucible; finally, the carbon-containing raw material components in the repair material, the block repair material and the binder can be converted into a graphite material with higher strength by graphitization treatment, thereby improving the compatibility of the block repair material and the graphite crucible, thereby improving the high temperature resistance and mechanical strength of the graphite crucible and extending the service life of the graphite crucible. The above-mentioned graphite crucible repair method is simple and efficient. The repaired graphite crucible has excellent high temperature resistance, volume density and mechanical strength, and can reduce the damage and cracking of the graphite crucible during use, thereby reducing the risk of kiln blockage and ensuring the smooth operation of the production line and the stability of production capacity. In addition, no harmful substances need to be added during the entire repair process, which is environmentally friendly and meets the requirements of sustainable development.

[0087] The preparation method of the present application is described in detail below with reference to the examples:

[0088] Step S100, processing the crack of the graphite crucible and opening a plurality of threaded holes on the surface of the graphite crucible.

[0089] It should be noted that the processing methods for the cracks at different positions of the crucible are also different. For example, when the crack of the crucible is on the side wall, you can choose to use a machining center or a CNC milling machine to process the crack on the side of the crucible, cut the notch, and process a dovetail buckle on the side of the crucible, and open multiple threaded holes on the side of the crucible; when the crack of the crucible is at the bottom, you can choose to use drilling and tapping to process the crack at the bottom of the crucible, and open multiple threaded holes at the bottom of the crucible. The specific processing method can be selected according to the actual situation and is not limited here.

[0090] Step S200: coating the graphite crucible repair material on the crack of the graphite crucible, and combining the block-shaped repair material and the graphite crucible with graphite bolts.

[0091] In the above scheme, the repair material coated on the crack of the graphite crucible has excellent adhesion. Under the action of the repair material, the block repair material and the graphite crucible are tightly combined by using graphite bolts, which can not only ensure the firmness of the repair, but also simplify the repair process and improve the repair efficiency.

[0092] In some embodiments, the preparation method of the graphite crucible repair material includes: weighing 10 to 35 parts by weight of coke raw material and / or graphite tailings and 1 to 5 parts by weight of polysaccharide compound (yellow dextrin) respectively, and mixing them evenly to obtain a mixture A; then weighing 5 to 15 parts by weight of aluminum silicate, 10 to 20 parts by weight of acrylic emulsion, 5 to 10 parts by weight of polyethylene glycol, 5 to 10 parts by weight of dioctyl phthalate (DOP) and 1 to 5 parts by weight of isocyanate respectively, and mixing them evenly to obtain a mixture B; then adding mixture A to mixture B at a rate of 0.1 kg / min to 0.3 kg / min, mixing evenly, and obtaining a graphite crucible repair material.

[0093] In another embodiment, a method for preparing a graphite crucible repair material comprises: weighing 10 to 35 parts by weight of coke raw material and / or graphite tailings (median particle size D50 ≤ 3 μm), 5 to 1 part by weight of aluminum silicate, and 10 to 20 parts by weight of acrylic emulsion respectively; adding aluminum silicate and acrylic emulsion to the coke raw material and / or graphite tailings at a rate of 0.1 kg / min to 0.3 kg / min, stirring evenly, and obtaining a graphite crucible repair material.

[0094] In some embodiments, the preparation method of the block repair material includes: weighing 10 to 35 parts by weight of coke raw material and / or graphite tailings, 5 to 15 parts by weight of aluminum silicate, 10 to 20 parts by weight of acrylic emulsion, 5 to 10 parts by weight of polyethylene glycol, 5 to 10 parts by weight of dioctyl phthalate (DOP), 1 to 5 parts by weight of polysaccharide compound (yellow dextrin) and 1 to 5 parts by weight of isocyanate; kneading the above materials; heating and pressing the kneaded product to obtain a block repair material.

[0095] It should be noted that in the present application, during the actual use of the repair material and the block repair material, the component raw materials can be used in the same weight ratio or in different weight ratios, which can be selected according to actual needs and is not limited here.

[0096] In some embodiments, the method of adding the above materials during the preparation of the block repair material includes: adding 5 to 15 parts by weight of aluminum silicate, 10 to 20 parts by weight of acrylic emulsion, 5 to 10 parts by weight of polyethylene glycol, 5 to 10 parts by weight of dioctyl phthalate (DOP) and 1 to 5 parts by weight of isocyanate to a kneading device according to a mass ratio, and then adding a mixture of 10 to 35 parts by weight of coke raw material and / or graphite tailings and 1 to 5 parts by weight of a polysaccharide compound (yellow dextrin) to the kneading device at a rate of 0.1 kg / min to 0.3 kg / min for mixing.

[0097] In some embodiments, the temperature of the kneading treatment is 100°C~260°C, specifically 100°C, 120°C, 150°C, 180°C, 200°C, 220°C, 240°C, 250°C or 260°C, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0098] In some embodiments, the rotation speed of the kneading process is 60 rpm to 120 rpm, specifically 60 rpm, 70 rpm, 80 rpm, 90 rpm, 100 rpm, 110 rpm or 120 rpm, etc., and of course, it can also be other values ​​within the above range, which is not limited here.

[0099] In the present application, the temperature and rotation speed of the kneading process are controlled within the above range, which can improve the mixing uniformity of the raw materials of each component and improve the quality and performance of the block repair material.

[0100] In some embodiments, the pressure of the heating and pressing treatment is 800T to 1200T, specifically 800T, 850T, 900T, 950T, 1000T, 1050T, 1100T, 1150T or 1200T, etc., and of course, other values ​​within the above range are also possible, which are not limited here. Controlling the pressure of the heating and pressing treatment within the above range can promote the uniform distribution of components in the block repair material, improve the density of the block repair material, reduce cracks and defects in the block repair material, and improve the compressive strength and flexural strength of the block repair material.

[0101] In some embodiments, the temperature of the heating and pressing treatment is 2000°C~2400°C, specifically 2000°C, 2100°C, 2200°C, 2300°C or 2400°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0102] In some embodiments, the time for heating and pressing treatment is 60 min to 90 min, specifically 60 min, 65 min, 68 min, 70 min, 75 min, 80 min, 85 min, 86 min, 88 min or 90 min, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0103] In the present application, the temperature and time of the heating and pressing treatment are controlled within the above-mentioned range, which is beneficial to promote the bonding between the component particles in the block repair material, reduce the porosity of the block repair material, and increase the density of the block repair material, which is beneficial to improve the uniformity and consistency of the block repair material, and reduce the occurrence of cracks and breakage of the block repair material during use, thereby improving the compressive strength and flexural strength of the repaired graphite crucible.

[0104] In some embodiments, the pressure increase rate and pressure release rate of the heating and pressing treatment are each independently less than 10 T / min, and can be specifically 9.8 T / min, 9.5 T / min, 8.9 T / min, 8.5 T / min, 7 T / min, 6.4 T / min, 5 T / min, 4 T / min, 3 T / min, 2 T / min or 1 T / min, etc., and of course, it can also be other values ​​within the above range, which are not limited here.

[0105] In some embodiments, the inert ambient atmosphere includes at least one of nitrogen, argon, helium, and neon.

[0106] Step S300, placing the graphite crucible in an inert environment at 1000°C-1150°C for coke removal treatment.

[0107] In the above scheme, impurities introduced during the graphite crucible repair process can be removed by coke removal, thereby ensuring the quality and safety of the negative electrode product. At the same time, the repair gap can be effectively filled to improve the mechanical strength of the graphite crucible.

[0108] In some embodiments, the temperature of the decoking treatment is 1000°C ~ 1150°C, specifically 1000°C, 1020°C, 1050°C, 1080°C, 1100°C, 1120°C or 1150°C, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0109] In some embodiments, the heating rate of the decoking treatment is 0.2°C / min~1°C / min, specifically 0.2°C / min, 0.3°C / min, 0.4°C / min, 0.5°C / min, 0.6°C / min, 0.7°C / min, 0.8°C / min, 0.9°C / min or 1°C / min, etc. Of course, it can also be other values ​​within the above range, which are not limited here.

[0110] In some embodiments, the time for the decoking treatment is 1 h to 4 h, specifically 1 h, 1.5 h, 1.8 h, 2 h, 2.5 h, 3 h, 3.5 h, 3.8 h or 4 h, etc. Of course, it can also be other values ​​within the above range, which are not limited here.

[0111] Step S400, in a vacuum environment, the graphite crucible is impregnated with a binder at 200°C-700°C, and then the temperature is raised to 2400°C-2800°C for graphitization.

[0112] In some embodiments, the binder includes at least one of an asphalt solution, an acrylic emulsion, an aqueous polyurethane, an emulsion, and a polyvinyl alcohol (PVA) emulsion. It is understood that the above binder can be converted into a graphite carbon material with higher strength after high-temperature graphitization treatment, thereby improving the high temperature resistance and mechanical strength of the crucible and extending the service life of the crucible.

[0113] In some embodiments, the binder includes 8 to 15 parts by weight of aluminum silicate, 10 to 20 parts by weight of acrylic emulsion, and 1 to 10 parts by weight of dioctyl phthalate.

[0114] Optionally, the aluminum silicate in the binder can be 8 parts by weight, 8.5 parts by weight, 9 parts by weight, 10 parts by weight, 11 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight or 15 parts by weight, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0115] Optionally, the acrylic emulsion in the adhesive can specifically be 10 parts by weight, 11 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight, 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight or 20 parts by weight, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0116] Optionally, the dioctyl phthalate (DOP) in the adhesive may be 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight or 10 parts by weight.

[0117] In the present application, aluminum silicate, acrylic emulsion and dioctyl phthalate (DOP) are configured into a binder according to the above-mentioned weight ratio. The binder has excellent adhesion. After entering the pores of the graphite crucible, the repair effect of the graphite crucible can be further improved, and the volume density and strength of the graphite crucible can be improved. The carbon-containing raw material components in the binder can be converted into higher-strength graphite carbon materials after high-temperature graphitization treatment, thereby improving the high temperature resistance and mechanical strength of the graphite crucible and extending the service life of the Yancheng graphite crucible.

[0118] In some embodiments, the vacuum degree in the vacuum environment is less than 500 Pa, and may specifically be 490 Pa, 450 Pa, 400 Pa, 350 Pa, 300 Pa, 280 Pa, 200 Pa, 150 Pa, 100 Pa or 50 Pa, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0119] In some embodiments, the cooling rate from the decoking treatment to the immersion treatment is 0.2°C / min~1°C / min, specifically 0.2°C / min, 0.3°C / min, 0.4°C / min, 0.5°C / min, 0.6°C / min, 0.7°C / min, 0.8°C / min, 0.9°C / min or 1°C / min, etc. Of course, it can also be other values ​​within the above range, which are not limited here.

[0120] In some embodiments, the temperature of the immersion treatment is 200°C~700°C, specifically 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C or 700°C, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0121] In some embodiments, the immersion treatment time is 1 h to 4 h, specifically 1 h, 1.5 h, 1.8 h, 2 h, 2.5 h, 3 h, 3.5 h, 3.8 h or 4 h, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0122] In the present application, the temperature and time of the immersion treatment are controlled within the above range, which can reduce the viscosity of the binder and make it easier for the binder to penetrate into the pores of the graphite crucible, thereby reducing the porosity of the graphite crucible and improving the volume density and strength of the graphite crucible.

[0123] In some embodiments, the temperature of the graphitization treatment is 2400°C~2800°C, specifically 2400°C, 2450°C, 2500°C, 1080°C, 1100°C, 1120°C or 1150°C, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0124] In some embodiments, the time of graphitization treatment is 2h~4h, specifically 2h, 2.2h, 2.5h, 2.8h, 3h, 3.5h, 3.6h, 3.8h or 4h, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0125] In some embodiments, the heating rate of the graphitization treatment is 0.2°C / min~1°C / min, specifically 0.2°C / min, 0.3°C / min, 0.4°C / min, 0.5°C / min, 0.6°C / min, 0.7°C / min, 0.8°C / min, 0.9°C / min or 1°C / min, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0126] The present application controls the temperature and time of the graphitization treatment within the above range, so that the carbon-containing material in the graphite crucible repair material, the block repair material and the binder is converted into a graphite material with higher strength, further improving the graphitization degree of the graphite crucible, which can significantly improve the high temperature resistance and mechanical properties of the graphite crucible and extend the service life of the graphite crucible.

[0127] In some embodiments, after the graphitization treatment, the repair method further includes: cooling the graphite crucible to room temperature and then taking it out for surface grinding until the surface of the graphite crucible is smooth. After the surface of the repaired graphite crucible is ground, the surface of the crucible is smooth and has no protrusions, and has high strength and durability, which can meet the needs of various industrial applications.

[0128] Example 1

[0129] Graphite crucible side wall cracking:

[0130] (1) Preparation of a graphite crucible repair material: 15 parts by weight of natural spherical graphite (median particle size D50 ≤ 3 μm) and 1.2 parts by weight of yellow dextrin were weighed respectively by weight and mixed evenly to obtain a mixture A; 11.5 parts by weight of aluminum silicate, 14.4 parts by weight of acrylic emulsion, 8.5 parts by weight of polyethylene glycol, 6.4 parts by weight of dioctyl phthalate (DOP) and 3.2 parts by weight of isocyanate were weighed respectively by weight and mixed evenly to obtain a mixture B; then the mixture A was added to the mixture B at a rate of 0.2 kg / min and mixed evenly to obtain a graphite crucible repair material.

[0131] (2) Preparation of block repair material: 7 parts by weight of aluminum silicate, 19 parts by weight of acrylic emulsion, 7.5 parts by weight of polyethylene glycol, 6.7 parts by weight of dioctyl phthalate (DOP) and 3.8 parts by weight of isocyanate were weighed and added to a kneading device, and then a mixture containing 30 parts by weight of natural spherical graphite (median particle size D50≤3μm) and 4.2 parts by weight of yellow dextrin was added to the kneading device at a rate of 0.1kg / min for mixing until the mixture is uniform, wherein the temperature of the kneading device is controlled to be 260°C and the speed is 120rpm. After the mixed material is cooled to room temperature, it is placed in a vacuum hot press and hot pressed at 2400°C and 800F for 3h to obtain a block repair material, and the block repair material is processed to form a plurality of bolt through holes and dovetail buckles on its surface.

[0132] (3) Use a machining center to process the cracks on the side of the graphite crucible, cut out the notch, and process the corresponding dovetail buckle, and make threaded holes to ensure that the notch is flat.

[0133] (4) The graphite crucible repair material prepared in step (1) is evenly coated on the machined notch of the graphite crucible, and a graphite bolt (such as Figure 2 The block repair material obtained in step (2) is combined with the graphite crucible, and the block repair material forms a certain fit with the notch.

[0134] (5) Weigh 9 parts by weight of aluminum silicate, 15 parts by weight of acrylic emulsion and 6 parts by weight of dioctyl phthalate (DOP) and mix them evenly to obtain a binder; place the graphite crucible repaired in step (4) in a vacuum pressure impregnation device, first increase the temperature to 1100°C at 1°C / min, then introduce nitrogen to perform a decoking treatment, and keep the temperature for 4 hours; then reduce the temperature to 700°C at 1°C / min, add the binder, control the vacuum degree in the impregnation device to 300Pa~500Pa, and keep the temperature for 1 hour; then increase the temperature to 2600°C at 1°C / min to perform a graphitization treatment, and keep the temperature for 4 hours, then reduce the temperature to room temperature, and take out the graphite crucible.

[0135] (6) Grinding: Use a file or grinder to grind the surface of the graphite crucible to remove surface impurities until it is smooth.

[0136] Figure 1 Schematic diagram of the structure of the block repair material prepared in Example 1 of the present application; Figure 1 As shown, the surface of the block repair material is provided with a plurality of bolt through holes and a dovetail buckle. The setting of the dovetail buckle can release stress and ensure that the junction between the graphite crucible notch and the block repair material can withstand a larger external force, thereby improving the strength of the crucible.

[0137] Figure 2 This is a schematic diagram of the structure of the graphite bolt provided in Example 1 of the present application.

[0138] Figure 3 This is a schematic diagram of the crucible provided in Example 1 of the present application after processing; Figure 3 As shown, the surface of the graphite crucible is provided with a plurality of threaded holes and a dovetail buckle.

[0139] Figure 4 Schematic diagram of the combination of the block repair material and the graphite crucible provided in Example 1 of the present application; Figure 4 As shown, the block repair material and the graphite crucible are tightly and seamlessly combined together by graphite bolts.

[0140] Example 2

[0141] Graphite crucible side wall cracking:

[0142] The difference from Example 1 is:

[0143] (1) Preparation of graphite crucible repair material: 18 parts by weight of coke raw material (median particle size D50 ≤ 3 μm) and 2.2 parts by weight of yellow dextrin were weighed respectively by weight and mixed evenly to obtain a mixture A; 12.5 parts by weight of aluminum silicate, 13.4 parts by weight of acrylic emulsion, 7.5 parts by weight of polyethylene glycol, 8.4 parts by weight of dioctyl phthalate (DOP) and 4.2 parts by weight of isocyanate were weighed respectively by weight and mixed evenly to obtain a mixture B; then the mixture A was added to the mixture B at a rate of 0.2 kg / min and mixed evenly to obtain a graphite crucible repair material.

[0144] (2) Preparation of block repair material: 7 parts by weight of aluminum silicate, 17 parts by weight of acrylic emulsion, 8.5 parts by weight of polyethylene glycol, 6.7 parts by weight of dioctyl phthalate (DOP) and 2.8 parts by weight of isocyanate were weighed and added to a kneading device, and then a mixture containing 35 parts by weight of coke raw material (median particle size D50≤3μm) and 3.2 parts by weight of yellow dextrin was added to the kneading device at a rate of 0.1kg / min for mixing until the mixture is uniform, wherein the temperature of the kneading device is controlled to be 260°C and the speed is 120rpm. After the mixed material is cooled to room temperature, it is placed in a vacuum hot press and hot pressed at 2400°C and 800F for 3h to obtain a block repair material, and the block repair material is processed to form a plurality of bolt through holes and dovetail buckles on its surface.

[0145] Example 3

[0146] Graphite crucible side wall cracking:

[0147] The difference from Example 1 is:

[0148] (1) Preparation of graphite crucible repair material: 8 parts by weight of coke raw material, 8 parts by weight of natural spherical graphite (median particle size D50≤3 μm) and 2.2 parts by weight of yellow dextrin were weighed respectively and mixed evenly to obtain a mixture A; 12.5 parts by weight of aluminum silicate, 13.4 parts by weight of acrylic emulsion, 7.5 parts by weight of polyethylene glycol, 8.4 parts by weight of dioctyl phthalate (DOP) and 4.2 parts by weight of isocyanate were weighed respectively and mixed evenly to obtain a mixture B; then the mixture A was added to the mixture B at a rate of 0.2 kg / min and mixed evenly to obtain a graphite crucible repair material.

[0149] (2) Preparation of block repair material: 9.9 parts by weight of aluminum silicate, 18 parts by weight of acrylic emulsion, 9.5 parts by weight of polyethylene glycol, 7.7 parts by weight of dioctyl phthalate (DOP) and 3.8 parts by weight of isocyanate were weighed and added to a kneading device, and then a mixture containing 13 parts by weight of coke raw material, 19 parts by weight of natural spherical graphite (median particle size D50≤3μm) and 1.2 parts by weight of yellow dextrin was added to the kneading device at a rate of 0.1kg / min for mixing until the mixture is uniform, wherein the temperature of the kneading device is controlled to be 260°C and the speed is 120rpm. After the mixed material is cooled to room temperature, it is placed in a vacuum hot press and hot pressed at 2400°C and 800F for 3h to obtain a block repair material, and the block repair material is processed to form a plurality of bolt through holes and dovetail buckles on its surface.

[0150] Example 4

[0151] Wear of graphite crucible bottom:

[0152] (1) Preparation of graphite crucible repair material: 15 parts by weight of coke raw material (median particle size D50 ≤ 3 μm) and 1.7 parts by weight of yellow dextrin were weighed respectively by weight and mixed evenly to obtain a mixture A; 12.5 parts by weight of aluminum silicate, 19 parts by weight of acrylic emulsion, 7.5 parts by weight of polyethylene glycol, 6.5 parts by weight of dioctyl phthalate (DOP) and 3.2 parts by weight of isocyanate were weighed respectively by weight and mixed evenly to obtain a mixture B; then the mixture A was added to the mixture B at a rate of 0.2 kg / min and mixed evenly to obtain a graphite crucible repair material.

[0153] (2) Preparation of block repair material: 5 parts by weight of aluminum silicate, 18.5 parts by weight of acrylic emulsion, 7.5 parts by weight of polyethylene glycol, 6.5 parts by weight of dioctyl phthalate (DOP) and 3.8 parts by weight of isocyanate were weighed and added to a kneading device, and then a mixture containing 33 parts by weight of coke raw material (median particle size D50≤3μm) and 4.3 parts by weight of yellow dextrin was added to the kneading device at a rate of 0.1kg / min for mixing until the mixture is uniform, wherein the temperature of the kneading device is controlled to be 260°C and the speed is 120rpm. After the mixed material is cooled to room temperature, it is placed in a vacuum hot press and hot pressed at 2400°C and 800F for 3h to obtain a block repair material, and the block repair material is processed to form a plurality of bolt through holes on its surface.

[0154] (3) Use drilling and tapping to process the crack at the bottom of the crucible, and open multiple threaded holes at the bottom of the crucible.

[0155] (4) The repair material prepared in step (1) is evenly coated on the crack of the graphite crucible, and a graphite bolt (such as Figure 6 The block-shaped repair material obtained in step (2) is combined with the graphite crucible, and the block-shaped repair block and the groove form a certain fit.

[0156] (5) Place the graphite crucible repaired in step (4) in a vacuum pressure impregnation device, first heat it to 1100°C at a rate of 1°C / min, then introduce nitrogen to perform decoking treatment, and keep it warm for 4 hours; then cool it to 700°C at a rate of 1°C / min, add the asphalt solution, and control the vacuum degree in the impregnation device to 300Pa~500Pa, and keep it warm for 1 hour; then heat it to 2600°C at a rate of 1°C / min to perform graphitization treatment, and keep it warm for 4 hours, then cool it to room temperature and take out the graphite crucible.

[0157] (6) Grinding: Use a file or grinder to grind the surface of the graphite crucible to remove surface impurities until it is smooth.

[0158] Figure 5A schematic diagram of the structure of the block repair material provided in Example 4 of the present application; Figure 5 As shown, a plurality of bolt through holes are provided on the surface of the block-shaped repair material.

[0159] Figure 6 This is a schematic diagram of the structure of the graphite bolt provided in Example 4 of the present application.

[0160] Figure 7 This is a schematic diagram of the structure of the graphite crucible provided in Example 4 of the present application after processing; Figure 7 As shown, the crack at the bottom of the graphite crucible is processed by drilling and tapping to form a hole, and the bottom of the graphite crucible has a plurality of threaded holes.

[0161] Figure 8 Schematic diagram of the combination of the block repair material and the graphite crucible provided in Example 4 of the present application; Figure 8 As shown, the block repair material is tightly combined with the bottom of the graphite crucible through graphite bolts.

[0162] Example 5

[0163] Wear of graphite crucible bottom:

[0164] The difference from Example 4 is:

[0165] (1) Preparation of graphite crucible repair material: 17 parts by weight of natural spherical graphite (median particle size D50 ≤ 3 μm) and 1.2 parts by weight of yellow dextrin were weighed respectively by weight and mixed evenly to obtain a mixture A; 10.5 parts by weight of aluminum silicate, 18.4 parts by weight of acrylic emulsion, 6.5 parts by weight of polyethylene glycol, 7.4 parts by weight of dioctyl phthalate (DOP) and 3.2 parts by weight of isocyanate were weighed respectively by weight and mixed evenly to obtain a mixture B; then the mixture A was added to the mixture B at a rate of 0.2 kg / min and mixed evenly to obtain a graphite crucible repair material.

[0166] (2) Preparation of block repair material: 14.3 parts by weight of aluminum silicate, 17.5 parts by weight of acrylic emulsion, 8.5 parts by weight of polyethylene glycol, 6.7 parts by weight of dioctyl phthalate (DOP) and 3.8 parts by weight of isocyanate were weighed and added to a kneading device, and then a mixture containing 29 parts by weight of natural spherical graphite (median particle size D50≤3μm) and 4.2 parts by weight of yellow dextrin was added to the kneading device at a rate of 0.1kg / min for mixing until the mixture is uniform, wherein the temperature of the kneading device is controlled to be 260°C and the speed is 120rpm. After the mixed material is cooled to room temperature, it is placed in a vacuum hot press and hot pressed at 2400°C and 800F for 3h to obtain a block repair material, and the block repair material is processed to form a plurality of bolt through holes on its surface.

[0167] Example 6

[0168] Graphite crucible side wall cracking: (1) Preparation of graphite crucible repair material: Weigh 19 parts by weight of natural spherical graphite (median particle size D50 ≤ 3 μm), 13 parts by weight of aluminum silicate, and 19 parts by weight of acrylic emulsion respectively; add aluminum silicate and acrylic emulsion to the natural spherical graphite at a rate of 0.2 kg / min, stir evenly, and obtain a graphite crucible repair material.

[0169] (2) Preparation of block repair material: 14.3 parts by weight of aluminum silicate, 17.5 parts by weight of acrylic emulsion, 7.5 parts by weight of polyethylene glycol, 7.7 parts by weight of dioctyl phthalate (DOP) and 3.8 parts by weight of isocyanate were weighed and added to a kneading device, and then 32 parts by weight of natural spherical graphite (median particle size D50≤3μm) was added to the kneading device at a rate of 0.1kg / min for mixing until the mixture is uniform, wherein the temperature of the kneading device is controlled to be 260°C and the speed is 120rpm. After the mixed material is cooled to room temperature, it is placed in a vacuum hot press and hot pressed at 2400°C and 900F for 3h to obtain a block repair material, and the block repair material is processed to form a plurality of bolt through holes on its surface.

[0170] (3) Use a machining center to process the cracks on the side of the graphite crucible, cut out the notch, and process the corresponding dovetail buckle, and make threaded holes to ensure that the notch is flat.

[0171] (4) The graphite crucible repair material prepared in step (1) is evenly coated on the machined notch of the graphite crucible, and a graphite bolt (such as Figure 2 The block repair material obtained in step (2) is combined with the graphite crucible, and the block repair material forms a certain fit with the notch.

[0172] (5) Place the graphite crucible repaired in step (4) in a vacuum pressure impregnation device, first heat it to 1100°C at a rate of 1°C / min, then introduce nitrogen to perform decoking treatment, and keep it warm for 4 hours; then cool it to 700°C at a rate of 1°C / min, add the asphalt solution, and control the vacuum degree in the impregnation device to 300Pa~500Pa, and keep it warm for 1 hour; then heat it to 2600°C at a rate of 1°C / min to perform graphitization treatment, and keep it warm for 4 hours, then cool it to room temperature and take out the graphite crucible.

[0173] (6) Grinding: Use a file or grinder to grind the surface of the graphite crucible to remove surface impurities until it is smooth.

[0174] Example 7

[0175] Wear of graphite crucible bottom:

[0176] (1) Preparation of graphite crucible repair material: 14.6 parts by weight of natural spherical graphite (median particle size D50 ≤ 3 μm), 12 parts by weight of aluminum silicate, and 17 parts by weight of acrylic emulsion were weighed respectively; aluminum silicate and acrylic emulsion were added to the natural spherical graphite at a rate of 0.2 kg / min and stirred evenly to obtain a graphite crucible repair material.

[0177] (2) 13.3 parts by weight of aluminum silicate, 16.5 parts by weight of acrylic emulsion, 7.5 parts by weight of polyethylene glycol, 7.7 parts by weight of dioctyl phthalate (DOP) and 3.8 parts by weight of isocyanate were weighed and added to a kneading device, and then 33 parts by weight of natural spherical graphite (median particle size D50≤3μm) was added to the kneading device at a rate of 0.1kg / min for mixing until the mixture was uniform, wherein the temperature of the kneading device was controlled to be 260°C and the speed was 120rpm. After the mixed material was cooled to room temperature, it was placed in a vacuum hot press and hot pressed for 3 hours at 2400°C and 1000F to obtain a block repair material, and the block repair material was processed to form a plurality of bolt through holes on its surface.

[0178] (3) Use drilling and tapping to process the crack at the bottom of the crucible, and open multiple threaded holes at the bottom of the crucible.

[0179] (4) The repair material prepared in step (1) is evenly coated on the crack of the graphite crucible, and a graphite bolt (such as Figure 6 The block-shaped repair material obtained in step (2) is combined with the graphite crucible, and the block-shaped repair block and the groove form a certain fit.

[0180] (5) Place the graphite crucible repaired in step (4) in a vacuum pressure impregnation device, first heat it to 1100°C at a rate of 1°C / min, then introduce nitrogen to perform decoking treatment, and keep it warm for 4 hours; then cool it to 700°C at a rate of 1°C / min, add the asphalt solution, and control the vacuum degree in the impregnation device to 300Pa~500Pa, and keep it warm for 1 hour; then heat it to 2600°C at a rate of 1°C / min to perform graphitization treatment, and keep it warm for 4 hours, then cool it to room temperature and take out the graphite crucible.

[0181] (6) Grinding: Use a file or grinder to grind the surface of the graphite crucible to remove surface impurities until it is smooth.

[0182] Comparative Example 1

[0183] The repair agent includes: 20 parts by weight of natural spherical tailings; 19 parts by weight of asphalt particles; 9 parts by weight of coke powder; 22 parts by weight of phenolic resin; 23 parts by weight of epoxy resin; and 5 parts by weight of alcohol.

[0184] Pretreatment step: placing the crack of the crucible in an oxidizing atmosphere at 1100° C. for 30 minutes; the oxidizing atmosphere includes oxygen and nitrogen, and the oxygen content is 30%;

[0185] Cool the crucible to 10°C;

[0186] Coating step: coating the repairing agent on the crack of the crucible;

[0187] Drying step: placing the crucible in nitrogen at a first temperature of 150° C. for 6 h;

[0188] Sintering step: placing the crucible in a vacuum environment at a second temperature of 1300° C. for 2 h.

[0189] Test Method

[0190] 1. Volume density test of graphite crucible:

[0191] 1. Take the sample provided by the crucible manufacturer or the sample obtained from the crucible as the sample, remove the oxide scale of the sample and measure its length, width and thickness respectively. Measure the length 4 times, the width and thickness 3 times respectively, and take the average value to get the sample length l, sample width w and sample thickness b;

[0192] 2. Dry the sample in an electric heating constant temperature box at 105°C~110°C for 1h;

[0193] 3. Place the sample in a desiccator and weigh it after cooling to room temperature. The mass of the sample is recorded as m, accurate to 0.1g;

[0194] 4. Calculation of results:

[0195] 4.1. The sample volume is calculated according to formula (1):

[0196] V = bwl (1)

[0197] In formula (1):

[0198] V-sample volume, in cm³;

[0199] b-specimen thickness, in cm;

[0200] w-specimen width, in cm;

[0201] l-sample length, in cm;

[0202] 4.2. Sample volume density d j Calculate according to formula (2):

[0203] d j =m / V

[0204] Where:

[0205] d j - Sample volume density, in g / cm³;

[0206] m-sample mass, in g;

[0207] V-sample volume, in cm³.

[0208] 2. Graphite crucible flexural strength test:

[0209] 1. Load pressure cutter head radius r1 = 4.5 ± 0.5 (mm), support cutter edge radius r2 = 1 ± 0.5 (mm);

[0210] 2. The two supporting blades should be in the same plane and parallel. The load pressure cutter head should be parallel to the two supporting blades and should be able to move up and down in the vertical direction of the parallel planes of the two supporting blades and be located in the middle position;

[0211] 3. The sample size meets the requirements of JB / T8133.1;

[0212] 4. Distance between two support blades L S According to Table 1:

[0213] Table 1

[0214]

[0215] Test steps:

[0216] (1) Check that the mechanical zero point is at zero position, all components are normal, and the distance between the two support blades is L. S Comply with the requirements of Table 1;

[0217] (2) Check the sample size. The measurement accuracy of dimensions w and b is 0.5%;

[0218] (3) If Fig. 9 As shown, the specimen is placed symmetrically on two supporting blades, and the distance between the two supporting blades is L S , the specimen size L is perpendicular to the knife edge, the size w is parallel to the knife edge, the load pressure head is in the middle of the specimen, that is, the pressure is applied between the two knife edges, and the pressure direction is F;

[0219] (4) Start the testing machine and apply load evenly and slowly for no less than 5 seconds until the specimen breaks, and read the destructive force at this time;

[0220] (5) Calculation results:

[0221] The flexural strength is calculated according to the following formula:

[0222]

[0223] Where:

[0224] δ z -Flexural strength (in MPa);

[0225] F- load at break (N);

[0226] L S -Support blade distance (mm);

[0227] w-specimen width, (mm);

[0228] b- sample thickness, (mm).

[0229] 3. Compressive strength test of graphite crucible

[0230] Test conditions:

[0231] 1. The sample should not have defects such as edge loss, corner loss, cracks and bulges;

[0232] 2. Loading should be done slowly during the test, with a speed of 4mm / min~10mm / min.

[0233] Test steps:

[0234] (1) Adjust the testing machine to normal state and return the pointer to zero;

[0235] (2) If Fig.10 As shown, place the sample 1 at the center of the lower support surface 2, and the loading direction F should be perpendicular to the axial direction of the extruded product;

[0236] (3) Start the testing machine and load the material according to the above test conditions until it is completely broken, and read the destructive force F at this time;

[0237] (4) Calculation of results:

[0238] The flexural strength is calculated according to the following formula:

[0239] δ s =F / S

[0240] Where:

[0241] δ s -Compressive strength (MPa);

[0242] F-total load of specimen failure (N);

[0243] S-specimen cross-sectional area (mm²).

[0244] The above test results are detailed in Table 2:

[0245] Table 2 Performance test results of graphite crucible

[0246]

[0247] According to the test data in Table 2, the graphite crucible repair method provided by the present application can ensure the firmness of the repair by processing the crack of the graphite crucible and tightly connecting the block repair material and the graphite crucible with graphite bolts under the action of the graphite crucible repair material, thereby simplifying the repair process and improving the repair efficiency; and then placing the graphite crucible under a protective atmosphere for coke removal treatment, through which the impurities introduced in the graphite crucible repair process can be removed, thereby ensuring the quality and safety of the negative electrode product, and at the same time, the repair gap can be made smaller. Effective filling to improve the mechanical strength of the graphite crucible; then the graphite crucible is impregnated with a binder in a vacuum environment, and the binder can be filled into the pores of the graphite crucible through impregnation treatment under a vacuum environment, thereby improving the volume density and strength of the graphite crucible; finally, the carbon-containing raw material components in the repair material, block repair material and binder can be converted into a graphite material with higher strength through graphitization treatment, thereby improving the compatibility of the block repair material and the graphite crucible, thereby improving the high temperature resistance and mechanical strength of the graphite crucible and extending the service life of the graphite crucible. The above-mentioned graphite crucible repair method is simple and efficient. The repaired graphite crucible has excellent high temperature resistance, volume density and mechanical strength, which can reduce the damage and cracking of the graphite crucible during use, thereby reducing the risk of kiln blockage and ensuring the smooth operation of the production line and the stability of production capacity. In addition, no harmful substances need to be added during the entire repair process, which is environmentally friendly and meets the requirements of sustainable development.

[0248] According to the test data in Table 2, the graphite crucible repair materials used in Examples 6 and 7 do not contain polyethylene glycol, dioctyl phthalate (DOP), yellow dextrin and isocyanate, and the porosity of the repaired graphite crucible increases, the bulk density, degree of graphitization, compressive strength and flexural strength all decrease, and the number of uses of the repaired graphite crucible also decreases. According to the test data in Table 2, the crucible repair material and the crucible repair method used in Comparative Example 1 are different from those in the present application, the porosity of the repaired crucible increases, the bulk density, degree of graphitization, compressive strength and flexural strength all decrease, and the number of uses of the repaired graphite crucible decreases significantly.

[0249] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A graphite crucible repair material, characterized in that: The graphite crucible repairing material comprises: 10-35 parts by weight of coke raw material and / or graphite tailings; 5-15 parts by weight of aluminum silicate; 10-20 parts by weight of acrylic emulsion; 5-10 parts by weight of polyethylene glycol; 5-10 parts by weight of dioctyl phthalate; 1-5 parts by weight of polysaccharide compound; and 1-5 parts by weight of isocyanate; Wherein, the median particle size of the coke raw material and / or the graphite tailing is ≤5 μm.

2. The graphite crucible repair material according to claim 1, characterized in that: The polysaccharide compound includes yellow dextrin.

3. The graphite crucible repairing material according to any one of claims 1 to 2, characterized in that: The repair material is subjected to heating and pressing treatment to obtain a block-shaped repair material; wherein the thickness of the block-shaped repair material is 2 mm to 10 mm, and a plurality of bolt through holes are opened on the surface of the block-shaped repair material.

4. The graphite crucible repair material according to claim 3, characterized in that: The heating and pressing process includes at least one of the following features: (1) The pressure of the heating and pressing treatment is 800T~1200T; (2) The temperature of the heating and pressing treatment is 2000°C to 2400°C; (3) The heating and pressing treatment time is 60 min to 90 min; (4) The pressure increase rate and pressure release rate of the heating and pressing process are independently less than 10 T / min.

5. A method for repairing a graphite crucible, characterized in that: The crucible is repaired using the graphite crucible repair material according to any one of claims 3 to 4, and the repair method comprises the following steps: Processing the crack of the graphite crucible and opening a plurality of threaded holes on the surface of the graphite crucible; Applying a graphite crucible repair material to the crack of the graphite crucible, and combining the block-shaped repair material with the graphite crucible using a graphite bolt; Placing the graphite crucible in an inert atmosphere environment at 1000° C. to 1150° C. for coke removal treatment; In a vacuum environment, the graphite crucible is impregnated with a binder at 200°C-700°C, and then heated to 2400°C-2800°C for graphitization.

6. The method for repairing a graphite crucible according to claim 5, characterized in that: The repair method includes at least one of the following features: (1) The inert atmosphere includes at least one of nitrogen, argon, helium and neon; (2) The heating rate of the decoking treatment is 0.2°C / min to 1°C / min; (3) The de-coking process lasts for 1 to 4 hours; (4) The vacuum degree in the vacuum environment is less than 500 Pa; (5) The cooling rate from the decoking treatment to the immersion treatment is 0.2°C / min to 1°C / min; (6) The immersion treatment time is 1h~4h; (7) The graphitization treatment time is 2h~4h; (8) The heating rate of the graphitization treatment is 0.2°C / min~1°C / min; (9) After the graphitization treatment, the repair method further includes: cooling the graphite crucible to room temperature and then taking it out for surface polishing until the surface of the graphite crucible is smooth.

7. The method for repairing a graphite crucible according to claim 6, characterized in that: The binder includes at least one of asphalt solution, acrylic emulsion, water-based polyurethane, emulsion, and polyvinyl alcohol emulsion; and / or, the binder includes 8 to 15 parts by weight of aluminum silicate, 10 to 20 parts by weight of acrylic emulsion, and 1 to 10 parts by weight of dioctyl phthalate.

Citation Information

Patent Citations

  • Crucible repairing agent and crucible repairing method

    CN117327470A

  • High-temperature-resistant crucible

    CN107324817A

  • Graphite crucible repairing paste and graphite crucible repairing method

    CN112143384A